2020
DOI: 10.1177/1745691620931461
|View full text |Cite
|
Sign up to set email alerts
|

A Call for Greater Attention to Culture in the Study of Brain and Development

Abstract: Despite growing research on neurobiological development, little attention has been paid to cultural and ethnic variation in neurodevelopmental processes. We present an overview of the current state of developmental cognitive neuroscience with respect to its attention to cultural issues. Analyses based on 80 publications represented in five recent meta-analyses related to adolescent developmental neuroscience show that 99% of the publications used samples in Western countries. Only 22% of studies provided a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 156 publications
3
28
0
Order By: Relevance
“…Samples in studies of intimate relationships were overwhelmingly drawn from Western countries, with 73% stemming from the United States and an additional 22% coming from other Western countries, while only 5% came from Asia, Africa, Latin America, and Israel combined. This is in line with the meta-science literature, which consistently finds that more than 90% of samples are drawn from Western, industrialized nations (Arnett, 2008;Nielsen et al, 2017;Qu et al, 2020). Additionally, participants in U.S.based studies of intimate relationships were overwhelmingly likely to be White, consistent with participant demographics in other areas of psychology (Nielsen et al, 2017;Qu et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Samples in studies of intimate relationships were overwhelmingly drawn from Western countries, with 73% stemming from the United States and an additional 22% coming from other Western countries, while only 5% came from Asia, Africa, Latin America, and Israel combined. This is in line with the meta-science literature, which consistently finds that more than 90% of samples are drawn from Western, industrialized nations (Arnett, 2008;Nielsen et al, 2017;Qu et al, 2020). Additionally, participants in U.S.based studies of intimate relationships were overwhelmingly likely to be White, consistent with participant demographics in other areas of psychology (Nielsen et al, 2017;Qu et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…With regard to socioeconomic status, a few other meta-science studies did attempt to examine income, but concluded that so few studies reported this information that they were unable to draw any inferences about the socioeconomic makeup of participants (Qu et al, 2020;Rad et al, 2018). We also found a high degree of missing income data (76%) but due to the very large corpus of studies included in our review we did have enough data to analyze participant income levels.…”
Section: Socioeconomic Statusmentioning
confidence: 88%
See 2 more Smart Citations
“…Greater attention to culture has been called for in developmental research [ 102 ]. The current study demonstrates 11-month-old infants’ sensitivity to differences in culture-specific emotional expressions when combined with differences in racial appearance, but that this sensitivity is more apparent for anger and surprise (novelty effect) than for happiness (familiarity effect).…”
Section: Discussionmentioning
confidence: 99%